A multi-vocal review: Characterization of food safety trainings across LMICs and influence on intervention efficacy - Pal, H.; Bettridge, J.; Mutua, Florence; Grace, Delia (2022)
OBJECTIVES: Food Safety Education can improve hygiene practices in wet markets, and hence help reduce foodborne disease burden. A variety of training techniques have been reported in LMICs in the past decade. This study aimed to identify associations between reported efficacy of a training intervention and training design, including materials used, to identify the most effective and sustainable training strategies.